Widespread outdoor exposure to uncompensable heat stress with warming - Yuanchao Fan; Kaighin A. McColl (Communications Earth & Environment)
Abstract Previous studies projected an increasing risk of uncompensable heat stress indoors in a warming climate. However, little is known about the timing and extent of this risk for those engaged in essential outdoor activities, such as water collection and farming. Here, we employ a physically-based human energy balance model, which considers radiative, wind, and key physiological effects, to project global risk of uncompensable heat stress outdoors using bias-corrected climate model outputs. Focusing on farmers (approximately 850 million people), our model shows that an ensemble median 2.8% (15%) would be subject to several days of uncompensable heat stress yearly at 2 (4) °C of warming relative to preindustrial. Focusing on people who must walk outside to access drinking water (approximately 700 million people), 3.4% (23%) would be impacted at 2 (4) °C of warming. Outdoor work would need to be completed at night or in the early morning during these events.